The Clinical Efficacy Analysis of Treatment With a Willis Covered Stent in Traumatic Pseudoaneurysm of the Internal Carotid Artery - Zhao, Yueyuan; Liu, Zhiwen; Sun, Ronghui; Pan, Li; Yang, Ming; Song, Jian; Ma, Lianting (Frontiers in Neurology, 2021)
Objective: To investigate the safety and efficacy of Willis covered stents (WCS) in the treatment of traumatic pseudoaneurysm of the cranial internal carotid artery (CICA). Methods: Fifteen patients with traumatic pseudoaneurysm of the intracranial segment of the ICA treated with the WCS system at our institution from 2013 to 2019 were analyzed retrospectively. Follow-up observation and digital subtraction angiography (DSA) examination were conducted 6 months after the treatment. Results: DSA performed immediately after stent deployment revealed that complete occlusion of the lesion was achieved in 13 patients and that endoleak occurred in two patients. In 12 patients, postoperative DSA examination indicated that the lesions were completely occluded. In two patients who had a second stent implantation at the break of the ICA, traumatic ICA rupture was essentially completely obstructed in 1 patient. The endoleak remained in one patient with carotid cavernous sinus fistula because the placement of the second stent system was difficult with his ICA tortuosity. No recurrence of aneurysms, hemorrhage, or other lesions was observed, and the patients' parent arteries were patent without stenosis. No procedure-related complications or ischemic strokes occurred during the follow-up period of 6 months. Conclusions: For treatment of traumatic pseudoaneurysm of the CICA, Willis covered stent implantation in some appropriate cases, is safe and effective. However, large-sample controlled studies and multicenter studies are needed for further confirmation.